The existence of informationally efficient markets when individuals are rational - Marc-Andreas Muendler (Center for Economic Studies and ifo Institute (CESifo), 2004)
A rational-expectations equilibrium with positive demand for financial information does exist under fully revealing asset price - contrary to a wide-held conjecture. Generalizing the common additive signal-return model with CARA utility to the family of distributions with moment generating functions, this paper shows that individual investors endowed with an average portfolio demand information in equilibrium if they can adjust portfolio size. More information diminishes the expected excess return of a risky asset so that investors who only have a choice of portfolio composition or whose asset endowments strongly differ from the average portfolio are worse off. Under fully revealing price, information market equilibria both with and without information acquisition are Pareto efficient.
Keywords: D82; G14; D83; 330; information; efficiency; financial markets; portfolio theory; Finanzmarkt; Gleichgewicht; Anlageverhalten; Rationale Erwartung; Informationseffizienz; Effizienzmarktthese; Portfolio-Management; Theorie